The development of sensory-perceptual processes of the psyche in conditions of norm and organic pathology (CP) - Romanenko, Oksana Viktorivna (Insight: the psychological dimensions of society, 2020)
The urgency of the problem of studying sensory-perceptualprocesses of the psyche is due to the need tofind ways to stimulate the activity of children in modernconditions, as well as improving the diagnosticsand correction of these processes in children with specialneeds as primary in the defect structure. The purpose of the article is to study theoretically and empiricallythe peculiarities of the development of sensory-perceptualprocesses of the psyche in the conditions of normand organic pathology (cerebral palsy). A comparativeanalysis of sensory-perceptual processes developmentin organic brain damage has been performed onthe basis of the consideration of the ontogenetic aspectof their study. It has been determined the way underthe influence of these processes the effects of otherlevels of the psyche are formed, the way each of themchanges and their interaction during the mental development of the child. The results of the studyof such an indicator of the development of sensory-perceptual processes as the accuracy of the executionof eye tasks are presented. Analysis of quantitativeindicators points out that the accuracy of the eyein younger pupils increases compared to preschoolage, but it is characterized by instability depending onthe type of task. At this age, children are already ableto establish the relationship of equality and inequalitybetween objects, but at the same time the indicatorsof dynamics are not yet as accurate as in adults. In additionto significant differences in eye accuracy, a greaterheterogeneity of the group of children with cerebralpalsy was found in comparison with healthy children inboth preschool and primary school age. This suggeststhat the development of eye has individual propertiesin children and it is associated with the process of naturalmaturation. Various disorders of the sensory-perceptualsphere in cerebral palsy are superimposed onthe individual measuring features of children, in particular,different degrees of coordination of hand and eye. Conclusion. Taking into account the individual specificsof the child’s mental development in relation tothe ratio of coordination of visual-motor functions willhelp to determine the appropriate means of correctionand create optimal conditions for subject, educationaland work activities.
Keywords: mental development, sensory-perceptual processes, anticipation, eye, children with cerebral palsy